(NgIDROGEOHIMIQ kAZAHSTANA (B/s - (NpORQDIN(B, (Nw(B. (Ni(B.s; (NsYDYKOW(B, (NvURUMBEK sYDYKOWI^s; (NdAWLETGALIEWA(B, (Nk(B. (Nm(B.s; (NvEWAGO(B, (NwLADIMIR sEMENOWI^s ((NaLMA(B-(NaTA (B:s (NnAUKA(B. (NkAZssr(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 186-190 (140 (NNAZW(B.)s
(NaWT(B. (NUKAZANY W OGL(B.s
(Nan kAZssr(B. (NiN(B-(NT GIDROGEOLOGII I GIDROFIZIKI IM(B. (Nu(B. (Nm(B. (NaHMEDSAFINAs
Keywords: (NwODY PODZEMNYE (B- (NgIDROHIMIQ (B- (NkAZsss